PENGUASAAN HURUF HIRAGANA DALAM PEMBELAJARAN BAHASA JEPANG SISWA KELAS X SMAN 9 PEKANBARU - Silvia Hildebertha Panjaitan; Merri Silvia Basri; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses the mastery of Hiragana letters in Japanese language learning for class X students of SMAN 9 Pekanbaru. In Japan there are 3 types of letters that must be learned, namely Hiragana, Katakana and Kanji. In this case the researcher chose Hiragana letters because Hiragana letters are very different from the alphabet letters that we usually learn. The purpose of this study was to describe the mastery of Hiragana letters to class X students of SMAN 9 Pekanbaru. The type of research used in this research is quantitative research with descriptive method. The population in this study were students of class X SMAN 9 Pekanbaru, amounting to 65 people. The sample in this study were students of class X IPA 4 SMAN 9 Pekanbaru, totaling 30 people. The data of this research are students' test scores in mastering Hiragana letters in Japanese language learning. Based on the results of the research conducted, it can be concluded that the mastery of Hiragana characters in Japanese learning in general is in the "adequate" qualification with an average obtained of 68,8.Key Words: The mastery, Japanese Characters, the Hiragana Letters